Overexpression of the metastasis‐associated gene MTA3 correlates with tumor progression and poor prognosis in hepatocellular carcinoma. Issue 8 (August 2017) - Wang, Chuanxi; Li, Guanzhen; Li, Jiamei; Li, Jie; Li, Tao; Yu, Jinyu; Qin, Chengyong
Abstract: Background and Aim: Hepatocellular carcinoma (HCC) is one of the most common and aggressive cancers in the world. However, there remains a lack of effective diagnostic and treatment markers. We aimed to explore metastasis‐associated protein 3 (MTA3) expression and function in HCC and its relationship with clinicopathological factors. Methods: We investigated the expression pattern and clinicopathological significance of MTA3 in 90 patients with HCC via immunohistochemistry and explored MTA3 function via gene knockdown of MTA3 . Results: MTA3 was overexpressed in HCC cell nuclei and downregulated in HCC cell cytoplasm. The former finding correlated with metastasis ( P = 0.010) and poor prognosis ( P = 0.018). In addition, deleting MTA3 inhibited HCC cell growth, invasion, and metastasis in vitro, as shown in the colony formation, migration, and wound‐healing assays. Conclusions: These results indicate that MTA3 is an oncogene of HCC, predicts poor prognosis of HCC, and may be a future marker of HCC treatment.